2017
DOI: 10.1038/icb.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the balance between necroptosis, apoptosis and inflammation by inhibitors of apoptosis proteins

Abstract: Understanding how inhibitor of apoptosis proteins (IAPs) regulate apoptosis and necroptosis has been fast-forwarded by the use of Smac mimetics (SMs) to deplete or inhibit the IAPs, specifically cIAP1, cIAP2 and XIAP. The loss or inhibition of cIAP1, cIAP2 and XIAP causes the majority of cells to be sensitized to death receptor induced cell death, such as with tumour necrosis factor (TNF). Mouse genetics shows that there is some functional redundancy and the use of SMs has allowed us to understand how changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 90 publications
0
46
0
Order By: Relevance
“…The best characterized members of the IAP family are x-linked IAP (xIAP) and cellular IAP1/2 (cIAP1/2) (Kocab and Duckett, 2016, Vasilikos et al., 2016). Smac mimetics are small compounds that are based on the IAP binding motif of Smac/Diablo (Figure 4A) and theoretically are also able to induce IAP degradation (Fulda, 2015, Fulda, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The best characterized members of the IAP family are x-linked IAP (xIAP) and cellular IAP1/2 (cIAP1/2) (Kocab and Duckett, 2016, Vasilikos et al., 2016). Smac mimetics are small compounds that are based on the IAP binding motif of Smac/Diablo (Figure 4A) and theoretically are also able to induce IAP degradation (Fulda, 2015, Fulda, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The TUNEL method is one of the most widely used detection methods for apoptosis in paraffin tissue sections. 27 Our TUNEL results showed that the apoptosis rate of the rats in the 4.5 and 8.5 mg/kg exposure groups was significantly higher than that in the control group. Therefore, we believe that long-term low-dose exposure of crotonaldehyde to male rats leads to apoptosis in rat lung tissue cells.…”
Section: The Changes Of Apoptosis-related Proteinsmentioning
confidence: 63%
“…Simplistically, TNF is believed to signal via the NF‐κB pathway as a default setting. When RIPK1 ubiquitylation is compromised, such as by inhibition or depletion of the E3 ubiquitin ligases, the inhibitor of apoptosis proteins (IAPs; reviewed in Vasilikos et al , 14 and Lalaoui and Brumatti, 15 ), RIPK1 can participate in death signalling. In cases where caspase‐3 and caspase‐8 activity operates, RIPK1, 16 CYLD 17 and possibly RIPK3 18 are cleaved and apoptosis prevails.…”
Section: The Necroptotic Pathwaymentioning
confidence: 99%